Experimental and numerical investigation on aerodynamic performance of a novel disc-shaped wind rotor for the small-scale wind turbine. (1st November 2018) - Xu, Zhang; Feng, Yan-Hao; Zhao, Chuang-Yao; Huo, Yu-Lei; Li, Sha; Hu, Xiao-Jian; Zhong, Ying-Jie
Highlights: Studied the aerodynamic performance of disc-shaped wind rotor for small wind turbine. Ranked the influence factors on power coefficient of the disc-shaped wind rotor. Provided optimum parameter combination for the highest power coefficient of 0.467. Studied the velocity field and wake characteristics under various parameters. Abstract: A series of novel disc-shaped wind rotors used in the small-scale wind turbine are redesigned with the inspiration from the eco whisper turbine. The aerodynamic parameters such as power coefficient and torque coefficient are obtained by numerical simulation and wind tunnel test. The tip speed ratio, pitch angle and opening angle are taken into consideration to account for the influences on the power coefficient. The specific case with pitch angle of 30° and opening angle of 45° is tested in a wind tunnel and simulated with different turbulence models for Reynolds number in the range of 6.8 × 10 4 –1.70 × 10 5, respectively. The results indicated that: (1) the numerical results based on the standard k - ω model agree well with the experimental results; (2) the orthogonal method shows the rank of influencing factors is pitch angle, opening angle and tip speed ratio, whose contributions to the power coefficient are about 66.36%, 18.53% and 11.43%, respectively; (3) the effects of both pitch angle and opening angle on power coefficient may be positive or negative, depending on the level of tip speed ratio; (4) as tip speed ratio increases, peak power coefficient can be achieved for an individual pitch angle or opening angle; (5) the value of tip speed ratio correspondent to the peak power coefficient decreases with decreasing pitch angle or opening angle; (6) the rotor with pitch angle of 20° and opening angle of 30° at a tip speed ratio of 1.4 provides the highest power coefficient of 0.47. The maximum power coefficient in the present paper is higher than most of the rotors in literature according to the comparison.